The Effect Of Using Instagram Application Toward Students’ Speaking Ability At The Eighth Grade Students Of MTS N 4 Bengkalis - Meilisa Dewi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
The purpose of this study was to determine the significant effect of using Instagram application students speaking ability. The researcher used quasi-experimental research design with quantitative approach. The population of the research was the students at the eighth grade students of MTS N 4 Bengkalis which has 120 participants consists of four classes. The researcher took two classes VII C and VII D as samples 60 participants, one class as an experimental class that was given treatment and another class as a control class that was not given treatment. The participants were selected by using cluster sampling. Techniques of collecting data was using an oral test. The result of the significant difference in students speaking ability post-test experiment class and post-test control class can be seen from the independent from SPSS 27, it showed that sig. (2-tailed) was smaller than 0.05 (0.000<0.05). It mean there was significant difference on students’ speaking ability between experiment class by using Instagram application and control class without using Instagram application. the researcher concluded that Instagram Application can used in the learning process to students’ speaking ability at school, especially at MTS N 4 Bengkalis.